Satisfaction ofworking people in Thailand in their usage of cloud storage systems - Chaiyasoonthorn, Wornchanok; Najantong, Kulapa; Chaveesuk, Singha (My University, 2018)
The purpose of this research was to investigate Satisfaction of working people in Thailand in their usage of cloud storage systems. The theories that this study was based on are Technology Acceptance Model 3 or TAM3, Unified Theory of Acceptance and Use of Technology Model or UTAUT and Service satisfaction. The sample group consisted of 400 working people in the central region of Thailand. Five hypotheses were formulated and tested by multiple linear regression statistic. Briefly, it was found that all of the four independent variables featured in the hypotheses: Perceived Usefulness, Perceived Ease of Use, Social Influence and Experience influent were significant to user satisfaction in terms of equitable service and progressive service. Some of the above independent variables also influenced user satisfaction in terms of timely service, ample service, and continuous service. The independent factor that did not influence user satisfaction in terms of timely service was Social Influence while the factor that did not do so in terms of ample service and continuous service was Perceived Usefulness.
Keywords: Cloud Computing; Cloud Storage System; Service Satisfaction; TAM3; UTAUT